Contributions of interpretive phenomenology to nursing research and nursing care - González Soto, Cinthia Elizabeth (2021)
Phenomenology as a research method represents one of the most valuable tools for nursing as it allows the study of the main phenomenon of interest to the discipline: the care of the human health experience. This paper aims to reflect on the contributions of interpretative phenomenology to nursing research and nursing care. It began with the analysis and reflection based on Martin Heidegger's approach to the use of interpretative phenomenology as a means of nursing research, to continue with the critical analysis of the literature on the topic addressed. In nursing, the act of caring involves not only the patient but also the nurse as a caregiver, where she must recognize her being and that of the other to understand and give meaning to the patient's reality, to achieve this interpretation requires dialogue and listening, essential elements in the nurse-patient care relationship, these two elements show the strong relationship between interpretive phenomenology and nursing care to build the meanings of care phenomena. The contributions of interpretive phenomenology to nursing care have been of great value for the improvement of the care provided, as they have made visible the most human needs of people, aspects that nursing has often neglected.